Az angolszász családtörténeti kutatások és hatásuk a magyarországi történeti demográfiára - Husz, Ildikó (Szociológiai Szemle, 2024)
In the 60s a new trend of research emerged at the borderline o f social science and social history, called family history. The basic issue of the trend was to study the relationship between the spread of the nuclear family, namely a family consisting of parents and their unmarried children, and the emergence of the modern Western society. The author of the paper surveys the Anglo-Saxon research into family history by presenting some of the major statements of Peter Laslett, challenging evolutionist theories for the first time. After a summary of the followers and critics of Laslett she analyses the influence of 'new social history' on the trend, and subsequently dwells upon the relationship between family history and the new trend of 'microhistory' which has appeared in social history during the past decade. The second part of the paper offers an assessment and summary of research into Hungarian family and household history.